OCCURANCE OF OVARIAN ACTIVITY IN POSTPARTUM ANOESTRUS INDEGENOUS COWS OF ASSAM FOLLOWING OLFACTORY CUES AND EXOGENOUS PROGESTERONE TREATMENT - BARUAH, ANUBHA; BARUAH, K K; SARMAH, B C; BHUYAN, S; KAKOTY, B K (The Indian Journal of Animal Reproduction, 2023)
A total of 28 indigenous Assam cows at 45 days postpartum were selected and divided into 4 groups astreatment groups (A, B, C ) and control (D) consisting of 7 animals in each group. The animals in group A wereisolated from the male and received daily oro nasal treatment with bull urine for 16 weeks, in group B, the cowswere kept with a fertile bull and were given oronasal treatment as in group A. In group C, the cows receivedexogenous hormone treatment and in group D, animals were left untreated. The postpartum cows attained earlyonset of estrus when received treatment i.e. in groupA69.40±3.9 days (50-80 days), in group B 67.30±4.4 days(52-84 days), in group C 33.60±1.54 days (29-40 days) in comparison to group D which was 254.86±11.42 dyas(196-294 days). All treated cows exhibited sign of estrus with 100% estrus response. The duration of estrus wasrecorded as 21. 71±0. 92 hours (17-24 hours) in group A, 22.86±1.08 hours (18-26 hours) in group B, 26.86±1.93hours (21-33 hours) in group C and 18. 76±0.97 hours (17-22 hours) in group D. Induction of estrus was accompaniedwith ovulatory response and the cows that ovulated conceived on insemination.
Keywords: Ovarian activity; Postpartum; Indigenous Cows; Norgestomet